Predicting sickness impact profile at six months after stroke: further results from the European multi-center CERISE study. (June 2015) - Stummer, C.; Verheyden, G.; Putman, K.; Jenni, W.; Schupp, W.; De Wit, L.
Abstract Purpose: To develop prognostic models and equations for predicting participation at six months after stroke. Methods: This European prospective cohort study recruited 532 consecutive patients from four rehabilitation centers. Participation was assessed at six months after stroke with the Sickness Impact Profile (SIP), which consists of a physical, psychosocial and independent dimension. Twenty-six independent variables on admission to the rehabilitation center and 13 additional variables measured at two months post stroke were included in the analysis. A multiple logistic regression analysis was conducted predicting good participation (SIP < 20%). Sensitivity, specificity, positive and negative predictive values were calculated. Results: The prognostic models for the three dimensions provided independent predictors containing demographics, complications, diagnostic, and disability measures. Sensitivity ranged from 64–84%, specificity 66–85%, positive predictive value 70–78%, and negative predictive value 76–87%. Barthel Index on admission, Euroqol Health State at two months and Caregiver Strain Index at two months were retained in all prediction models. Conclusions: A combination of variables was found in the prognostic models of the three dimensions of the SIP at six months after stroke. Already from the early beginning of stroke rehabilitation it seems important to focus on personal activities of daily living as well as caregivers' strain. Implications for Rehabilitation Prognostic factors predicting participation, measured by the three dimensions of the Sickness Impact Profile at six months post stroke include demographic variables, post-stroke complications, diagnostic parameters and disability measures. Significant prognostic variables for all three dimensions of the Sickness Impact Profile were a higher Barthel Index score on admission to the rehabilitation center, a higher Euroqol Health State score at two months post stroke and a lower Caregiver Strain Index score at two months post stroke. Early stroke therapy should therefore further emphasize rehabilitation of personal activities of daily living such as mobility, walking, feeding, dressing, and toilet use, as well as considering strategies to reduce caregiver strain such as giving support, providing information and training carers.